무릎 내측 구획 골관절염에서 초음파 유도하 경 반월상 연골 주사의 임상적 효과 - 정의엽(Eui Yub Jung); 왕준호(Joon Ho Wang); 이의섭(Eui-Sub Lee); 이성산(Sung-Sahn Lee); 소상연(Sang-Yeon So) (The journal of the Korean Orthopaedic Association, 2020)
목적: 무릎 내측 구획 골관절염 환자에서 초음파 유도하 무릎 관절강내 경 반월상 연골 주사를 소개하고 그 임상적 결과를 분석하고자 하였다. 대상 및 방법: 2019년 3월부터 2019년 7월까지 3개월 이상 무릎 통증이 지속되었던 무릎 내측 구획 골관절염 환자 중 초음파 유도하 경 반월상 연골 주사를 시행한 36명의 환자에 대해서 후향적으로 분석하였다. 초음파 유도하 척추 바늘을 이용하여 무릎관절강내 내측 구획에 corticosteroid와 국소마취제를 주사하였다. 시술 전, 1주, 4주, 8주째 신체진찰을 하였고 numeric pain rating scale (NRS), Lequesne index, Western Ontario and McMaster Universities Osteoarthritis (WOMAC) 점수를 측정하였다. 시간에 따른 NRS, Lequesne index, WOMAC 점수를 분석하였으며 상당한 호전이 있었던 환자들의 비율을 분석하였다. 또한 내측 구획 골관절염의 단계에 따른 NRS, Lequesne index, 상당한 호전이 있었던 환자들의 비율을 분석하였다. 결과: 시술 전과 비교하여 1주, 4주, 8주째 NRS와 Lequesne index는 감소하였고 8주째까지 통증 감소 효과는 차이 없이 지속되었다. 상당한 호전이 있었던 환자들의 비율은 1주, 4주, 8주째 각각 50.0%, 47.2%, 52.8%였으며 8주째까지 통증 감소 효과는 차이없이 지속되었다. 시술 전과 비교하여 1주, 4주, 8주째 WOMAC 점수는 감소하였고 8주째까지 차이 없이 감소가 지속되었다. 골관절염 1, 2단계 환자들에서 상당한 호전이 있었던 환자들의 비율이 골관절염 3, 4단계 환자들보다 1주, 4주, 8주째 유의하게 많았다(p＜0.05). 결론: 무릎 내측 구획 골관절염 환자에서 초음파 유도하 무릎 관절강내 경 반월상 연골 주사는 평균 8주 이상의 통증 감소 및 기능개선 효과를 보였다. 특히 내측 구획 골관절염 1, 2단계 환자에서는 통증 감소 효과가 더 컸다. Purpose: The purpose of this study was to introduce the ultrasound-guided transmeniscal injection in medial compartment knee osteoarthritis and analyze the clinical outcomes. Materials and Methods: The electronic medical records of 36 patients with medial compartment knee osteoarthritis who were treated with an ultrasound-guided transmeniscal injection from March 2019 to July 2019 were accessed for this retrospective review. Using an ultrasound guided spinal needle, the patients received an intra-articular steroid injection at the medial compartment of the knee. A physical examination was conducted at the initial visit (pre-injection), and at one week, four weeks, and eight weeks after the injection. The numeric pain rating scale (NRS), Lequesne index, and Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score were measured at each visit and analyzed over time. The percentage change of the patients who revealed substantial improvement was analyzed. The NRS, Lequesne index, and percentage of patients, who revealed substantial improvement over time classified by osteoarthritis grade, were analyzed. Results: The NRS and Lequesne index decreased at one week, four weeks, and eight weeks after the injection compared to the initial baseline, and the pain-relief effect continued without change until eight weeks. The percentage of patients who showed substantial improvement at one, four, and eight weeks was 50.0%, 47.2%, and 52.8%, respectively. The WOMAC scores decreased at one, four, and eight weeks compared to the initial baseline, and the decrease was continued without any difference until eight weeks. The percentage of patients with osteoarthritis stage 1 or 2 who revealed more than substantial improvement was significantly higher at one, four, and eight weeks than those with osteoarthritis stages 3 or 4 (p<0.05). Conclusion: In patients with medial compartment knee osteoarthritis, the pain reduction and functional improvement persisted for at least eight weeks after the ultrasound-guided transmeniscal injection at the medial compartment. In particular, patients with medial compartment osteoarthritis stage 1 or 2 showed more effective pain reduction. KCI Citation Count: 0